Green coal mining technique integrating mining-dressing-gas draining-backfilling-mining - Zhang, J.; Zhang, Q.; Spearing, Sam; Miao, X.; Guo, S.; Sun, Q. (Elsevier, 2016)
Aiming to address the following major engineering issues faced by the Pingdingshan No. 12 mine: (1) difficulty in implementing auxiliary lifting because of its depth (i.e., beyond 1000m); (2) highly gassy main coal seam with low permeability; (3) unstable overlying coal seam without suitable conditions for implementing conventional mining techniques for protective coal seam; and (4) predominant reliance on "under three" coal resources to ensure production output. This study proposes an integrated, closed-cycle mining-dressing-gas draining-backfilling-mining (MDGBM) technique. The proposed approach involves the mining of protective coal seam, underground dressing of coal and gangue (UDCG), pressure relief and gas drainage before extraction, and backfilling and mining of the protected coal seam. A system for draining gas and mining the protective seam in the rock stratum is designed and implemented based on the geological conditions. This system helps in realizing pressure relief and gas drainage from the protective seam before extraction. Accordingly, another system, which is connected to the existing production system, is established for the UDCG based on the dense medium-shallow trough process. The mixed mining workface is designed to accommodate both solid backfill and conventional fully mechanized coal mining, thereby facilitating coal mining, USCG, and backfilling. The results show that: The mixed mining workface length for the Ji15-31010 protected seam was 220m with coal production capacity 1.2million tons per year, while the backfill capacity of gangue was 0.5million tons per year. The gas pressure decreased from 1.78 to 0.35MPa, and the total amount of safely mined coal was 1.34million tons. The process of simultaneously exploiting coal and draining gas was found to be safe, efficient, and green. This process also yielded significant economic benefits.